2018
DOI: 10.1248/bpb.b18-00319
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and Pathophysiological Roles of Transient Receptor Potential Channels in Microglia-Related CNS Inflammatory Diseases

Abstract: Central nervous system (CNS) inflammation is a potential therapeutic target for neurodegenerative diseases. In recent years, a number of studies have focused on the links between neurodegenerative diseases and CNS glial cells, especially microglia. Microglia are the main resident immune cells in the CNS and represent approximately 10-15% of all CNS cells. Microglia play an important role in maintaining brain homeostasis at rest by surveying the environment, and engulfing apoptotic cells and debris in the healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…Neurotoxicity of NO overproduction in the brain has also been shown by several studies [16][17][18]. NO may play an important role in secondary neuronal damage after ischemia [19].…”
Section: Introductionmentioning
confidence: 67%
“…Neurotoxicity of NO overproduction in the brain has also been shown by several studies [16][17][18]. NO may play an important role in secondary neuronal damage after ischemia [19].…”
Section: Introductionmentioning
confidence: 67%
“…The increase [Ca 2+ ]i then induces mitochondrial dysfunction that leads to caspase activation, ROS and RNS production, microglia activation, and production of pro-inflammatory mediators (yellow arrows). cell death (Kim et al, 2006) and NADPH-oxidase-mediated production of ROS in microglia (Shirakawa and Kaneko, 2018), suggesting that a similar mechanism could operate in death of DNs in PD. For instance, TRPV1 antagonists such as capsazepine and iodo-resiniferatoxin inhibit DNs death in vivo and in vitro (Kim et al, 2005).…”
Section: Trps In Parkinson's Diseasementioning
confidence: 99%
“…It has been demonstrated that LPC increases phosphorylation of p38 MAPK in microglia, which was eliminated in TRPM2-KO. From these results, it is feasible to propose TRPM2 channels as potential therapeutic targets to inhibit excessive microglial activation, neuroinflammation, and, therefore, pain through modulation of p38 MAPK phosphorylation (Miyake et al, 2014;Jeong et al, 2017;Shirakawa and Kaneko, 2018).…”
Section: Trps Involvement In Pain Alzheimer's and Parkinson's Diseasesmentioning
confidence: 99%
See 2 more Smart Citations